Perkembangan Produksi Subsektor Perikanan di Sumatera Utara - Sri Endang Rahayu; Nel Arianty; Fajar Kurniawan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
The potential of the marine and fisheries sector in North Sumatra is very abundant but the production of fishery products is still not optimal. This is due to the low level of education and the technology used by fishermen which is still relatively simple so that their production results are less than optimal and the high costs of capture fisheries production. Then there are many problems faced by fishermen in increasing their capture fisheries production and the basic needs of fishermen with a value that fishermen must pay which is higher than the value received by fishermen. The purpose of this study was to analyze descriptively how the production of the fisheries sub-sector in North Sumatra is developing. The research approach used is a quantitative descriptive approach. Data collection techniques are documentation by taking secondary data. Data sources are from the Central Bureau of Statistics (BPS) and the Ministry of Maritime Affairs and Fisheries. In 2020, Central Tapanuli Regency is the largest capture fisheries producer in North Sumatra Province. The ups and downs of capture fisheries production in each district occur because of the unfavorable weather resulting in low fishing activity. This unfavorable weather occurs due to large sea waves and strong currents.